Penyuluhan Anemia Gizi Dengan Media Power Point Pada Remaja Di SMP Negeri 7 Tebas: Nutritional Anemia Counseling With Power Point Media in Adolescents at SMP Negeri 7 Tebas - Tara Anantasya; Elsa Fanny Budi; Nurhayati Safitri; Sudarti; Vebi Andriani; Yunita (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Anemia is one of the nutritional problems in the world that occurs not only in developing countries but also in developed countries. Low iron intake is common in people who consume less diverse foods, such as protein. The problems faced by partners today include the lack of adolescent knowledge about anemia, so it is necessary to provide counseling to provide knowledge to adolescents to prevent anemia in adolescents. Counseling activities on anemia were carried out at SMP N 7 Tebas. This counseling activity was carried out in October 2022. The target is the students of SMPN 7. Community service methods approach surveys, lectures, discussions. The result we obtained was that the students of SMPN 7 were able to understand about the prevention of anemia in adolescents. We recommend that students can prevent it by taking iron-boosting supplements, eating foods that will be rich in vitamin C and eating foods that contain iron.